Flood‐pulse disturbances as a threat for long‐living Amazonian trees. Issue 6 (19th June 2020) - Resende, Angélica F.; Piedade, Maria T. F.; Feitosa, Yuri O.; Andrade, Victor Hugo F.; Trumbore, Susan E.; Durgante, Flávia M.; Macedo, Maíra O.; Schöngart, Jochen
Summary: The long‐lived tree species Eschweilera tenuifolia (O. Berg) Miers is characteristic of oligotrophic Amazonian black‐water floodplain forests ( igapó ), seasonally inundated up to 10 months per year, often forming monodominant stands. We investigated E. tenuifolia ' growth and mortality patterns in undisturbed (Jaú National Park ‐ JNP) and disturbed igapós (Uatumã Sustainable Development Reserve ‐ USDR, downstream of the Balbina hydroelectric dam). We analysed age–diameter relationships, basal area increment (BAI) through 5‐cm diameter classes, growth changes and growth ratios preceding death, BAI clustering, BAI ratio, and dated the individual year of death ( 14 C). Growth and mortality patterns were then related to climatic or anthropogenic disturbances. Results were similar for both populations for estimated maximum ages (JNP, 466 yr; USDR, 498 yr, except for one USDR tree with an estimated age of 820 yr) and slightly different for mean diameter increment (JNP: 2.04 mm; USDR: 2.28 mm). Living trees from JNP showed altered growth post‐1975 and sparse tree mortality occurred at various times, possibly induced by extreme hydroclimatic events. In contrast with the JNP, abrupt growth changes and massive mortality occurred in the USDR after the dam construction began (1983). Even more than 30 yr after dam construction, flood‐pulse alteration continues to affect both growth and mortality of E. tenuifolia . Besides its vulnerability to anthropogenic disturbances, this species is also susceptible to long‐lasting dry and wet periods induced by climatic events, the combination of both processes may cause its local and regional extinction.